Risiko Kestabilan Lereng Akibat Gempabumi (Studi Area di Kecamatan Patuk, Kabupaten Gunungkidul) - Hari Suryana, Eka Priangga; Pramumidjojo, Subagyo; Satryarno, Iman (Universitas Muhammadiyah Yogyakarta, 2018)
The research about risk of slope stability as an effort to mitigate landslide slopes due to the earthquake, based on the earthquake of Jogja 2006 along the Opak River fault. The methods used in this study refers to the PERKA BNPB number 2 of 2012, which conducts a qualitative assessment of the landslide control parameters. Slope stability test is done as an effort to see the effect from earthquake to slope using SLOPE / W software. Test results at 3 locations, each slope in a stable state under normal conditions without earthquake. The first slope (1) in Patuk village has a value ofsafety factor is 2.45, while in earthquake condition has safety factor number is 1.27. The value of the safety factor on the second slope (2) in Ngoro-oro village under normal condition safety factor is 2.22 and the earthquake condition has value safety factor is 0.74. The third slope (3) in Ngoro-oro village has a safety factor number is 3.62 while in earthquake condition has value 1.95. The result of landslide risk calculation use first (1) scenario in Patuk sub-district generally has medium class, with yellow color in landslide risk map. Patuk villages has high class level for landslide risk map, meanwhile Terbah and Semoyo villages have low level class for landslide risk map. The slope in Patuk sub-district has stable conditions againts earthquake, but the change from slope material caused by weathering can made trigger landslide in future.